2013
DOI: 10.3389/fphar.2013.00136
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein mediated efflux limits substrate and drug uptake in a preclinical brain metastases of breast cancer model

Abstract: The blood–brain barrier (BBB) is a specialized vascular interface that restricts the entry of many compounds into brain. This is accomplished through the sealing of vascular endothelial cells together with tight junction proteins to prevent paracellular diffusion. In addition, the BBB has a high degree of expression of numerous efflux transporters which actively extrude compounds back into blood. However, when a metastatic lesion develops in brain the vasculature is typically compromised with increases in pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 51 publications
3
58
0
Order By: Relevance
“…These studies are now reaching clinical trials, an exciting landmark in targeted CNS therapeutics. Other groups are investigating inhibition of efflux mechanisms to maintain drug levels in the NVU (95,96). Successful modulation of these endogenous transport systems will prove critical to drug delivery in the NVU.…”
Section: Future Directionsmentioning
confidence: 99%
“…These studies are now reaching clinical trials, an exciting landmark in targeted CNS therapeutics. Other groups are investigating inhibition of efflux mechanisms to maintain drug levels in the NVU (95,96). Successful modulation of these endogenous transport systems will prove critical to drug delivery in the NVU.…”
Section: Future Directionsmentioning
confidence: 99%
“…While preclinical data indicate that p-glycoprotein (p-gp) mediated efflux kinetics are similar between normal BBB and BTB (Adkins et al, 2013), clinical data suggest p-gp expression in metastatic brain tumors is similar to that of primary, extracranial tumors and decreased compared to primary brain tumors (Gerstner and Fine, 2007). In a murine model, a non-p-gp substrate HER2/EGFR kinase inhibitor displayed modest but significantly better control of brain tumors compared with lapatinib (Nakayama et al, 2013), supporting the role of active drug efflux on pharmacokinetics and efficacy.…”
Section: Blood-brain Barrier: Time To Rethink Its Importance In Treatmentioning
confidence: 99%
“…In the case of epilepsy and neurodegenerative disorders such as Amyotrophic Lateral Sclerosis (ALS), studies have suggested that Pgp expression may be elevated [2,3], potentially further restricting the delivery of drugs and resulting in less therapeutic benefits [4]. Additionally, with brain tumors, Pgp can be overexpressed in both the semi-permeable “blood-tumor barrier” (BTB) but also in the plasma membrane of tumor cells [5,6]. Overexpression of this protein and other efflux pumps are linked to multi-drug resistance against several anticancer drugs [7] and can result in tumors developing cross resistance to other therapeutics.…”
Section: Introductionmentioning
confidence: 99%